Model of Local Wisdom Legal Source and State Law in Aceh Government - Zulfan, Zulfan (Indonesian Comparative Law Review, 2018)
The initial process of the peace agreement between Indonesian Government and Aceh Free Movement in 2005 was through sociological, philosophical, juridical and political considerations. The Free Aceh Movement attempted to reconstruct the source of local wisdom law in Law Number 11 the Year 2006 regarding Aceh Government. It means that the 1945 Constitution of the Republic of Indonesia recognizes and respects Aceh's special government units. Essentially, the arrangement of placing the model of the source of the law of local wisdom exists to be enforced as a unity of law and facts cannot be separated. Consequently, law and implementation re-quire unity of will. Why does the Free Aceh Movement love the arrange ments and practices of the old constitution and tradition? Because the source of Islamic Shariah, the foundation of the Aceh community life is articulated in the modern perspective of democratic and responsible state government. Basic aspirations of the specificity of Acehnese religious community life not only in the field of custom, cultural, social and political, but provide legal certainty in all affairs. The main target responds to the failure of state challenges to uphold the law, democracy, freedom of human rights and justice. The study was limited to how their wishes to change the concept of legal arrangements and practices worked in the real world, linking the legal unity with the facts of society to the two sets of legal documents governing Aceh. The study used normative approach, legal history, and comparative law. Juridically, there are two main goals to be achieved from the implementation of the arrangements and practices in this study. First, it places the differences and equations of both models of the source of local wisdom law and the design of state law. Secondly, it turns out that the concept of Acehnese legal culture highly values pluralism.